Erosion and sedimentation processes and river training works in Nepal - Upadhyay, S. P. (Journal of Nepal Geological Society, 1996)
This paper attempts to present an overview of erosion and sedimentation processes in Nepal. The rivers that flow through the Nepalese territory originate not only from different altitudes of the country but also have catchment areas lying in India and Tibetan region of the People's Republic of China, too. All the rivers ultimately join the Ganges. GLOF and erosion of the upper reaches of the catchment area are the major professes of sediment production. Depositional areas are mainly the foot hills and wide river channels. The author also tries to demonstrate the impact of erosion and sedimentation on the geo environment in Nepal. Finally, mitigative measures and importance of river training works are highlighted.